UV curable heat resistant epoxy acrylate coatings - Firdous, Habib; Bajpai, Madhu (Publishing House of Lviv Polytechnic National University, 2010)
Polymeric materials are exposed to high temperatures that results in lowering of the film integrity. A blend of an epoxy resin with the silicone acrylate resin was developed to provide high heat resistance UV cured coatings. Earlier siliconized epoxy coatings had been developed by conventional curing. But due to environmental awareness, high productivity rate, low process costs and energy saving UV curable coatings are enjoying considerable growth. Thermally stable UV cured coatings used in the present study were developed from silicone acrylate and epoxy acrylate resin with different diluents and photoinitiator. Such coatings provide higher thermal stability (693 K) along with physical and chemical resistance. In addition, such coatings can also be obtained by using functional amino silanes. The resin developed provides a simple and practical solution to improve heat resistance along with physical and chemical resistance of the UV cured coatings. The purpose of this research paper is to develop UV curable heat resistant coatings by the combination of inorganic and organic polymer, taking epoxy acrylate as a base resin. В роботі вивчено отримання термостабільних УФ-затверджених покриттів, виходячи з силікон-акрилатів та епоси-акрилатних смол, в присутності різних за природою розчинників іфотоініціаторів. Встановлено, що такі покриття характеризуються високою термостабільністю (693 К) та проявляють фізичну і хімічну стійкість. Запропонований метод дає можливість отримувати термостійкі покриття, виходячи як із органічного, так і неорганічного полімеру, в тому числі функцій них аміносиланів, беручи за основу епоксидний акрилат.
УФ-затверджені термостійкі епокси-акрилатні покриття
Keywords: heat resistance; silicone acrylate; UV-curing; термостійкість; силіконоакрилат; УФ-затвердження